Peer Coaching : Unlocking the Power of Collaboration. - Foltos, Lester (Les) J. (Joseph) (SAGE Publications, 2013)
Teachers are better together!For schools to implement the classroom changes the future demands, teachers must learn how to collaborate effectively. This book details the deeply-researched peer coaching method formulated by Les Foltos and implemented in over 40 countries with powerful results. Its insights include: How peer coaching that makes a difference involves much more than just offering advice. How a coaching relationship is first built on trust, and then on the willingness to take risks. Why peer coaching should focus on adapting teaching methods to the technological future o.